Investigation of the identity of the nucleophile initiating the hydrolysis of phosphate esters catalyzed by dinuclear mimics of metallohydrolases - Brown, Joshua James; Gahan, Lawrence R.; Schöffler, Anne; Krenske, Elizabeth H.; Schenk, Gerhard (Journal of inorganic biochemistry, 2016)
di-Zinc(II) complexes of the ligands 2,6-bis((bis(2-methoxyethyl)amino)methyl)-4-methylphenol (HL1), 2,6-bis(bis(hydroxyethyl)aminomethyl)-4-methylphenol (HL2) and 2,6-bis((hydroxyethyl)(methoxyethyl)-aminomethyl)-4-methylphenol (HL3) have been prepared and characterized. The three ligands differ in their donor types, having ether donors (HL1), alkoxido donors (HL2) and both ether and alkoxido donors (HL3). These differences allowed an investigation into the role of the potential nucleophiles in the hydrolysis reaction with the phosphodiester substrate bis(2,4-dinitrophenyl)phosphate (BDNPP). In addition, the di-Mg(II) complex of ligand HL2 was prepared in order to examine the potential for Mg(II) to replace Zn(II) in these biomimetic systems. Kinetically relevant pKa values for the three di-Zn(II) complexes were determined to be 7.14 and 9.21 for [Zn2(L1)(CH3COO)2](PF6), 7.90 and 10.21 for [Zn2(L2)(CH3COO)2](BPh4) and 8.43 and 10.69 for [Zn2(L3)(CH3COO)2](BPh4). At the respective pH optima the relevant catalytic parameters are kcat=5.44(0.11)×10−5s−1 (Km=5.13(0.92) mM), 2.60(0.87)×10−4s−1 (Km=5.49(1.51) mM) and 1.53(0.27)×10−4s−1 (Km=2.14(0.50) mM) for [Zn2(L1)(CH3COO)2](PF6), [Zn2(L2)(CH3COO)2](BPh4) or [Zn2(L3)(CH3COO)2](BPh4), respectively. The di-Mg(II) complex was found to be unreactive in the hydrolysis reaction with BDNPP under the conditions employed. Computational methods using the [Zn2(L2)(CH3COO)2](BPh4) complex were used to discriminate between different possible mechanistic pathways. The DFT calculations indicate that an alkoxido-mediated pathway in the complexes formed with ligands L2 or L3 is unlikely, because it induces significant distortion of the Zn2(L) unit; a direct attack by a coordinated hydroxide is preferred in each of the three systems studied here. The calculations also revealed the important role of ligand structural rigidity.